2005
DOI: 10.1002/jbm.b.30251
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of the fibrin clot extension on different implant surfaces: An in vitro study

Abstract: The aim of the present study was a quantitative evaluation of the in vitro fibrin clot extension on different implant surfaces. Forty-five disk-shaped commercially pure Grade 2 titanium samples with three different surface topographies (machined, DPS, and Plus) were used in the present study. For the quantitative evaluation of the fibrin clot, 30 specimens were used (10 per group); human whole blood was employed. Venous blood was drawn from three healthy adult volunteers, and 0.2 mL were immediately dropped on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 40 publications
4
41
1
4
Order By: Relevance
“…This strong relation between the activation of blood coagulation, acute infl ammation and osteogenesis suggests that thrombogenesis provides important stimuli for osseointegration of endosseous implants (Stanford, 2010). Several in vitro studies have addressed the infl uence of topographical (Park et al, 2001;Di Iorio et al, 2005) and physicochemical surface properties (Nygren et al, 1997;Hong et al, 1999;Eriksson and Nygren, 2001;Hong et al, 2005;Arvidsson et al, 2007) of Ti surfaces Alkali treatment of microrough titanium surfaces on the activation of blood coagulation, the adhesion of blood cells or the adsorption of plasma proteins. These studies indicate that native Ti is intrinsically highly thrombogenic due to strong contact activation (Hong et al, 1998;Hong et al, 1999;Arvidsson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This strong relation between the activation of blood coagulation, acute infl ammation and osteogenesis suggests that thrombogenesis provides important stimuli for osseointegration of endosseous implants (Stanford, 2010). Several in vitro studies have addressed the infl uence of topographical (Park et al, 2001;Di Iorio et al, 2005) and physicochemical surface properties (Nygren et al, 1997;Hong et al, 1999;Eriksson and Nygren, 2001;Hong et al, 2005;Arvidsson et al, 2007) of Ti surfaces Alkali treatment of microrough titanium surfaces on the activation of blood coagulation, the adhesion of blood cells or the adsorption of plasma proteins. These studies indicate that native Ti is intrinsically highly thrombogenic due to strong contact activation (Hong et al, 1998;Hong et al, 1999;Arvidsson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both topographical and physicochemical properties of the surfaces were reported to infl uence the activation of blood coagulation. Surface roughness, e.g., was reported to enhance platelet activation and blood clot retention (Park et al, 2001;Di Iorio et al, 2005;), while the physicochemical properties of Ti surfaces were shown to infl uence contact activation or the adhesion and activation of leukocytes properties (Nygren et al, 1997;Hong et al, 1999;Eriksson and Nygren, 2001;Hong et al, 2005;Arvidsson et al, 2007). However, variation of surface chemistry and topography were often coupled within these studies and experimental conditions and blood products used greatly varied between these studies, which limits their comparability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, studies have shown that rough surfaces can improve bone apposition and osteoconductivity more effectively than smooth surfaces, and surface roughness influences fibrin clot retention and is important for the early stages of osseointegration. 17,18 Recently, with the development of three-dimensional (3D) printing technology, a new implant made by direct laser fabrication (DLF) broadened the field of implant manufacturing. As a new manufacturing technique, DLF has been widely used in the medical domain for biocompatible orthopedic implants, dental implants, and 3D reconstruction plates used in bony defects.…”
mentioning
confidence: 99%
“…Tal procedimento potencializa a ativação das plaquetas e retém o coágulo de fibrina mais eficientemente do que em superfícies lisas, que são eventos importantes em estágios iniciais da integração de materiais com os tecidos biológicos in vivo (Di Iorio et al, 2005).…”
Section: Superfícies Modificadas Por Subtraçãounclassified